Spotlight on construction cost overrun research: Superficial, replicative and stagnated - Ahiaga-Dagbui, D.; Smith, S.; Love, Peter; Ackermann, Fran (2015)
Construction projects routinely overrun their cost estimates. A plethora of studies have thus been dedicated to investigating the root causes, sizes, distribution and nature of overruns. The causes range from a poor understanding of the impact of systemicity and complexity projects, unrealistic cost targets and misguided trade-offs between project scope, time and cost to suspicions of foul play and even corruption. In spite of the vast attention dedicated to the problem of cost overrun, there has been limited evidence to support the claim that the size or occurrence of cost overruns is reducing in practice. A review of the literature reveals that it may not be an exaggeration to claim that the bulk of our current cost overrun research may be largely inadequate and deficient to deal with the complexity posed by construction projects. This paper provides a critique of current cost overrun research and suggests that the adoption of systems thinking is required to better understand the nature of cost overruns. We explore some of the embedded methodological weaknesses in the approaches adopted in a majority of cost overrun research, particularly the lack of systems thinking and demonstrable causality. We reach the following conclusion-cost overrun research has largely stagnated in the refinement and advancement of the knowledge area. It has largely been superficial and replicative. A significant paradigm and methodological shift may be required to address this perennial and complex problem faced in construction project delivery.